(3OhQGdJecjf GdGbJUGOj ddeQCI aj ehGLgI eTcdI GdabQ (B: s (3OQGSI ejOGfjI Ydi YjfI ef GdfSGA GdYGedGJ HbQjI GdMQGfjI HeMGaXI GdLjRI (B= s The role of woman economic empowerment in front of the Problem poverty : A field study on a sample of the working Women in Haraneya village in Giza - (3fSQjf hMjO SdjeGfs; (3djdi cGed YHOGddg GdHgfSChj (B: s; (3eMeO ceGd GdJGHYj Sdje (B: s ((3GdbGgQI (B: s (3fSQjf hMjO SdjeGf (B: s, 2014)
(3JgOa GdOQGSI GdcTa Yf OhQ GdJecjf GdEbJUGOi ddeQCI GdYGedI HGdbWGY ZjQ GdQSei dehGLgI eTcdI GdabQ hGfWdbJ GdOQGSI ddELGHI Yf NeSI JSGDdGJ JHdhQJ ai(B: (3eGgh OhQ BdjGJ GdJecjf GdEbJUGOi ddeQCI GdYGedI HGdbWGY ZjQ GdQSei dehGLgI eTcdI GdabQ ?(B: (3heG gh hGbY GdJecjf GdEbJUGOi ddeQCI GdYGedI HGdbWGY ZjQ GdQSei ? (B:(3heG gi eYhbGJ GdJecjf GdEbJUGOi ddeQCI GdYGedI HGdbWGY ZjQ GdQSei?(B: (3heG gi ChVGY GdeQCI GdYGedI HGdbWGY ZjQ GdQSei ?(B: (3heGgi GdUYhHGJ GdJi JhGLg GdeQCI GdYGedI HGdbWGY ZjQ GdQSei? hbO GYJeOJ GdOQGSI Ydi GdefgL GdhUai h CSdhH OQGSI GdMGdI hOdjd GdebGHdI cCOGI dLeY GdHjGfGJ(B:(3hbOJe GNJjGQ YTQjf MGdI ddJWHjb eeKdI ai SJ YTQI MGdI HeUfY QeSjS ddSLGO GdHOhi hKdGK MGdGJ HeUfY GdYhGOdi hMGdI hGMOI HGdhMOI GdeYjTjI HbQjI GdMQGfjI (B:(3cTaJ GdOQGSI HTbjgG GdfXQi hGdJWHjbi Yf Cf GdBdjI GdChdi ddJecjf GdEbJUGOi GdJi KHJJ HGdOQGSI GdejOGfjI ai bQjI GdMQGfjI gi aJM CShGb LOjOI ddJShjbs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdCOGH (B- (3bSe GdGLJeGYs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJecjf GdEbJUGOis; (3GdabQs; (3GdeQCIs